Hemodialysis-Associated Infections: Treatment with Cephapirin - Berman, S. J. (1978)
Large doses of cephapirin (50 mg/kg) administered during the first and last half hours of routine hemodialysis produced effective antimicrobial serum concentrations for 48 h. Repetitive administration during five successive hemodialysis sessions did not result in accumulation or accelerated metabolism of cephapirin. Ten infectious episodes in nine patients were treated in this manner with good clinical results and no toxicity.